STRUKTUR MODAL DAN LIKUIDTAS DALAM MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BEI DENGAN MODERASI VARIABEL KEBIJAKAN DIVIDEN - Zainullah, Muhammad; Wahyuni, Ika; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
Retail companies, also known as retail, are companies whose activities sell goods and services directly to consumers. So this study aims to determine the Capital Structure and Liquidity in Affecting Firm Value in Retail Companies Listed on the Indonesia Stock Exchange with Moderation of Dividend Policy Variables. The method used in this research is descriptive quantitative. The population in this study is a retail company listed on the Indonesia Stock Exchange in 2018-2022. Purposive sampling is the sampling technique in this study. Data analysis and hypothesis testing in this study used the Structural Equation Model. The results of hypothesis testing using a statistical application, Smart PLS 3.0, the results showed that capital structure has a positive but insignificant effect on firm value and liquidity has a negative but insignificant effect on firm value, dividend policy has a positive but insignificant effect in moderating the effect of capital structure on firm value, and dividend policy has a positive but insignificant effect in moderating the effect of liquidity on firm value.